KUALITAS PELAYANAN PENGELOLA OBJEK WISATA TAMAN MARGASATWA DAN BUDAYA KINANTAN KOTA BUKITTINGGI - Haby Frisco; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Studies on the quality of management services in wildlife parks are still rarely researched. Therefore, this study aims to find out by measuring the quality of management services in the Wildlife Park and Kinantan Culture tourist object in the Bukittinggi City by using a quantitative descriptive method to analyze the issues raised. Data collection techniques used questionnaires to visitors, interviews with managers, and direct field observations. The sample used in this study was 100 respondents taken based on the calculation of the slovin formula and using the non-probability sampling method. Based on the results of the research and analysis that has been carried out, it can be concluded that the quality of management services in the Kinantan Wildlife and Cultural Park, Bukittinggi City, is in the good category and needs to be maintained. This is seen based on the five dimensions according to Pasuraman's theory, namely the dimensions of tangible, reliability, responsiveness, assurance, and empathy. Keywords: Quality of Service, Management, Wildlife Park and Kinantan Culture